2021
DOI: 10.1136/svn-2021-001119
|View full text |Cite
|
Sign up to set email alerts
|

Mobile stroke care expedites intravenous thrombolysis and endovascular thrombectomy

Abstract: BackgroundThe number of mobile stroke programmes has increased with evidence, showing they expedite intravenous thrombolysis. Outstanding questions include whether time savings extend to patients eligible for endovascular therapy and impact clinical outcomes.ObjectiveOur mobile stroke unit (MSU), based at an academic medical centre in upstate New York, launched in October 2018. We reviewed prospective observational data sets over 26 months to identify MSU and non-MSU emergency medical service (EMS) patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…These metrics lack external validity because of variable dispatch and transport criteria. To illustrate, Grunwald et al had the highest rate of transportation/dispatch but transported a much lower percentage of patients with a final cerebrovascular diagnosis (39.7%) than we have previously reported (59%) ( 7 , 23 ).…”
Section: Thrombolysis Metricsmentioning
confidence: 46%
See 1 more Smart Citation
“…These metrics lack external validity because of variable dispatch and transport criteria. To illustrate, Grunwald et al had the highest rate of transportation/dispatch but transported a much lower percentage of patients with a final cerebrovascular diagnosis (39.7%) than we have previously reported (59%) ( 7 , 23 ).…”
Section: Thrombolysis Metricsmentioning
confidence: 46%
“…Since mobile stroke units (MSU) were first described in 2003 in Germany, numerous studies have shown MSU care expedites intravenous thrombolysis and mechanical thrombectomy compared to standard emergency medical services ( 1 7 ). Recently, two large, prospective controlled trials have shown improved clinical outcomes 90 days after presentation with acute ischemic stroke in patients receiving MSU care as compared to traditional emergency medical services ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…MSU safety and efficacy have been reported in several studies [140][141][142]. Moreover, MSU seems to expedite IVT to facilitate EVT for patients with LVO [143]. However, the true impact of MSU on clinical outcomes is unclear, since most MSU studies have not reported clinical outcomes [143].…”
Section: Telemedicine and Mobile Stroke Unitsmentioning
confidence: 99%
“…Moreover, MSU seems to expedite IVT to facilitate EVT for patients with LVO [143]. However, the true impact of MSU on clinical outcomes is unclear, since most MSU studies have not reported clinical outcomes [143]. Two recent studies, a non-RCT and an RCT, reported that in patients with acute stroke who were eligible for rtPA, global disability at 3 months was lower with MSU compared to in-person professional stroke care [144, 145].…”
Section: Telemedicine and Mobile Stroke Unitsmentioning
confidence: 99%
“…First introduced in Germany in 2003 (2), MSUs are specialized ambulances equipped with stroke care teams, CT scanners and pointof-care laboratory testing devices, which allow for the prehospital diagnosis and treatment of acute stroke. In recent years, MSU utilization has been demonstrated to positively impact various dimensions of stroke care such as the speed and frequency of intravenous thrombolysis (IVT), and stroke outcome (3)(4)(5). So far, MSU services have been confined to research settings in either large metropolitan areas or sparsely populated rural regions and have been highly individualized according to local conditions, regulations and restrictions.…”
Section: Introductionmentioning
confidence: 99%